2018
DOI: 10.3389/fmars.2018.00098
|View full text |Cite
|
Sign up to set email alerts
|

Out of Sight, But Within Reach: A Global History of Bottom-Trawled Deep-Sea Fisheries From >400 m Depth

Abstract: Deep-sea fish species are targeted globally by bottom trawling. The species captured are often characterized by longevity, low fecundity and slow growth making them vulnerable to overfishing. In addition, bottom trawling is known to remove vast amounts of non-target species, including habitat forming deep-sea corals and sponges. Therefore, bottom trawling poses a serious risk to deep-sea ecosystems, but the true extent of deep-sea fishery catches through history remains unknown. Here, we present catches for gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 53 publications
0
30
1
Order By: Relevance
“…Clark et al (2007) reported nearly 2.3 million tons of fish removed by trawling globally with 900,000 tons from seamounts in the North Pacific. More recent data from the Food and Agriculture Organization of the United Nations reports 14.4 million tons of fish caught by trawling globally with 2.07 million tons removed from the North Pacific alone (Victorero et al, 2018b). This translates into large areas of seamounts where any coral and sponge assemblages present, along with their associated communities of invertebrates and fishes, would have been damaged or removed by these fishing activities.…”
Section: Introductionmentioning
confidence: 99%
“…Clark et al (2007) reported nearly 2.3 million tons of fish removed by trawling globally with 900,000 tons from seamounts in the North Pacific. More recent data from the Food and Agriculture Organization of the United Nations reports 14.4 million tons of fish caught by trawling globally with 2.07 million tons removed from the North Pacific alone (Victorero et al, 2018b). This translates into large areas of seamounts where any coral and sponge assemblages present, along with their associated communities of invertebrates and fishes, would have been damaged or removed by these fishing activities.…”
Section: Introductionmentioning
confidence: 99%
“…Another important step for advancing our understanding on deep-sea sponge grounds is to unravel the environmental parameters that shape their distribution, which in turn will facilitate the development of efficient conservation strategies (Howell et al, 2016;Johnson et al, 2018). This is of uttermost importance as deepsea sponges are slow-growing organisms which makes them particularly vulnerable to human activities such as bottom trawling (Kenchington et al, 2014;Pusceddu et al, 2014;Victorero et al, 2018) and oil and gas activities (Vad et al, 2018). Indeed, deep-sea sponge grounds fulfill the Food and Agriculture Organization of the United Nations (FAO) definition of Vulnerable Marine Ecosystems (VMEs) and have also been included in the Oslo/Paris Convention for the Protection of the Marine Environment of the North-East Atlantic (OSPAR) List of threatened and/or declining species and habitats in the northeast Atlantic (OSPAR, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Along with climate regulation, provisioning of food from fish stocks is one of the most critical ecosystem services provided by the deep sea (Thurber et al, 2014); these stocks are increasingly important to global food security (Victorero, Watling, Palomares, & Nouvian, 2018;Watson & Morato, 2013). However, warming and deoxygenation will simultaneously affect fishes by increasing metabolic rates and oxygen demand while limiting supply of oxygen to their tissues to meet increased demand for oxygen in low-oxygen environments (Holt & Jørgensen, 2015;Pörtner, Bock, & Mark, 2017;Pörtner & Knust, 2007).…”
mentioning
confidence: 99%